Attachment Avoidance Moderates the Relationship Among Acceptance of Sugar Relationships, Motivation, and Self-Esteem - Ipolyi, Dóra; Csányi, Edit; Láng, András; Meskó, Norbert (Frontiers in Psychology, 2021)
A sugar relationship is a monetary-based liaison between a wealthier older and an attractive younger person, the latter receiving expensive gifts or financial compensation in exchange for her or his sexual companionship. Attachment, motivation, self-esteem are all integrative parts of adult romantic and sexual relationships. There is relatively little empirical research on the psychological correlates of accepting attitudes towards sugar relationships. The aim of our research was to explore the relationship among acceptance of sugar relationship, attachment (avoidance, anxiety), motivation (extrinsic, intrinsic), and self-esteem. A total of 2409 Hungarian adults including 1980 younger participants (1804 women, 175 men, mean age = 21.17) and 429 older participants (290 men, 138 women, mean age = 48.86) completed an online test battery comprising four self-report measures. In the younger subsample, the only significant association obtained for acceptance of sugar relationships was its positive correlation with extrinsic motivation. In the older subsample, acceptance of sugar relationships positively correlated with all tested variables except self-esteem. A subsequent analysis revealed that attachment avoidance but not anxiety moderated the associations between the variables. Among younger participants, the negative effect of self-esteem and intrinsic motivation on accepting sugar relationships decreased with increasing attachment avoidance. Among older participants, the positive effect of extrinsic motivation on accepting sugar relationships decreased with increasing attachment avoidance. Results are discussed with regard to relational and sexual goals associated with adult attachment orientations.